OCCURRENCE AND DISTRIBUTION OF PELAGIC FISH EGGS AND LARVAE IN THE CHILKA LAKE DURING THE YEARS 1964 AND 1965 - Kowtal, G V (Indian Journal of Fisheries, 2011)
The Chilka lake forms a lucrative fishing ground. The fish fauna, fisheries and various aspects of fishery biology of the lake have received considerable attention but detailed investigations on fish eggs, larvae and juveniles of the lake are lacking. The occurrence and distribution of pelagic fish eggs and larvae form an important study in capture fisheries management as they provide valuable information on the spawning habits and habitats and availability of spawn in quality and quantity in time and space. In view of the proposals for foreshore reclamation of the Chilka lake the present studies assume added interest as they throw light on fish seed resources of some of the economic fishes. The life history studies of fishes are essential for the proper understanding of their recruitment to fishery from time to time and for formulating measures for conservation and development of fisheries. Works of Chaudhuri (1916, 1917, 1923), Hora (1920), Jones and Sujansinghani (1954), Mitra and Devasundaram (1954) and Jhingran et al. (1963) refer to the breeding habits, eggs, larvae and juveniles of some of the fishes of Chilka lake. Jhingran and Natarajan (1966) have briefly reviewed the eggs, larvae and juveniles of some of the important fishes encountered in the lake. The present paper deals with the occurrence and distribution of pelagic fish eggs and larvae of the Chilka lake during the years 1964 and 1965.